2019
DOI: 10.1080/15428052.2019.1640156
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Evolution of Haute Cuisine Chef´s Career

Abstract: This article reviews gender differences in the career paths of successful chefs, including barriers, success factors, and the entrepreneurial path. The research was developed in 2016-17, using an international survey carried out in Spain, France, and the United States among culinary students, cooks, and chefs who responded to a structured questionnaire based on pre-selected topics. The results show that a chef's career requires various sets of skills. They should be leaders, mentors, and entrepreneurs.They wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…It is worth pointing out that others have used either a smaller sample to interview (e.g. one chef in Traynor et al , 2021 and six in Albors-Garrigos et al , 2020) or a larger regional sample to study quantitatively (Aubke, 2014; Gergaud et al , 2011). Through this innovative methodology, our study is able to look at larger samples qualitatively and provides new insights on this elite group.…”
Section: Methods and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth pointing out that others have used either a smaller sample to interview (e.g. one chef in Traynor et al , 2021 and six in Albors-Garrigos et al , 2020) or a larger regional sample to study quantitatively (Aubke, 2014; Gergaud et al , 2011). Through this innovative methodology, our study is able to look at larger samples qualitatively and provides new insights on this elite group.…”
Section: Methods and Data Collectionmentioning
confidence: 99%
“…They related innovation to artistic aspiration, perceived newness, continuous and discontinuous conditions, learning and network and adaptation. Finally, the gender barriers in becoming a top chef are documented, but Albors-Garrigos et al (2020) empirical study found “feminine values” to be important factors in the success of six female top chefs. Our study answers these studies call for further research in a larger sample adopting a qualitative design (Albors-Garrigos et al , 2020; Traynor et al , 2021) on the processes of becoming a top chef (Gergaud et al , 2011; Stierand and Lynch, 2008).…”
Section: Context – Profession and Businessmentioning
confidence: 99%
“… Albors Garrigós et al (2020) carried out a study that analyzed the success factors and barriers faced by chefs in their career paths, as well as the differences between genders, in Spain, France, and the United States. According to the study, the career of a chef demands a range of skills.…”
Section: Gender Inequality and Women In The Culinary Professionmentioning
confidence: 99%
“…Druckman (2012) and Harris and Giuffre (2015) outline this role in their books on women chefs. Other authors (Albors-Garrigos et al, 2019) consider entrepreneurial activity as a critical enabler based on quantitative analysis.…”
Section: Journal Articlesmentioning
confidence: 99%